2017
DOI: 10.1098/rstb.2016.0034
|View full text |Cite
|
Sign up to set email alerts
|

Domestication impacts on plant–herbivore interactions: a meta-analysis

Abstract: One contribution of 18 to a theme issue 'Human influences on evolution, and the ecological and societal consequences'. For millennia, humans have imposed strong selection on domesticated crops, resulting in drastically altered crop phenotypes compared with wild ancestors. Crop yields have increased, but a long-held hypothesis is that domestication has also unintentionally decreased plant defences against herbivores. To test this hypothesis, we conducted a phylogenetically controlled meta-analysis comparing ins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
157
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 157 publications
(167 citation statements)
references
References 45 publications
10
157
0
Order By: Relevance
“…Plant cultivars had different resistance to herbivory by M. sexta , but this did not depend on plant domestication nor soil type. This is in general agreement with our previous findings that M. sexta exhibits cultivar‐ or species‐specific resistance (Li et al, ), but is in contrast to other findings that show reduced herbivory resistance in domesticated crops (Chen, Gols, & Benrey, ; Rodriguez‐Saona et al, ; Whitehead, Turcotte, & Poveda, ). We found that the parasitoid C. congregata was primarily attracted to damaged versus undamaged plants, and for these damaged plants, wasps preferred some cultivars over others, and wild plants grown in tomato soil over wild plants grown in non‐tomato soil.…”
Section: Discussionsupporting
confidence: 93%
“…Plant cultivars had different resistance to herbivory by M. sexta , but this did not depend on plant domestication nor soil type. This is in general agreement with our previous findings that M. sexta exhibits cultivar‐ or species‐specific resistance (Li et al, ), but is in contrast to other findings that show reduced herbivory resistance in domesticated crops (Chen, Gols, & Benrey, ; Rodriguez‐Saona et al, ; Whitehead, Turcotte, & Poveda, ). We found that the parasitoid C. congregata was primarily attracted to damaged versus undamaged plants, and for these damaged plants, wasps preferred some cultivars over others, and wild plants grown in tomato soil over wild plants grown in non‐tomato soil.…”
Section: Discussionsupporting
confidence: 93%
“…An understanding of these processes can help inform how to mitigate the impacts domestication/agriculture [31] empirical a comprehensive, phylogenetically controlled meta-analysis found that domestication influences the evolution of herbivore resistance, though the magnitude is highly variable. Furthermore, the evolution of plant defence traits was highly variable in direction and magnitude hunting/harvesting [32] review contrasting aquatic and terrestrial harvesting, the evolution of system-specific traits can negatively affect populations, but these effects can be mitigated through reduction of Then, from the standpoint of ecological and societal consequences, in §3 we ask: In which contexts will humaninduced evolution most alter .…”
Section: Introductionmentioning
confidence: 99%
“…However, the increase in growth rate through domestication and agronomic selection assumed to be driving this reduction has not been found in several studies (Cook & Evans, ; Evans, ; Preece et al., ; Welter, ), suggesting that changes in defence investment through domestication may not result from a trade‐off with growth rate. Additionally, some studies have not found a defence reduction through domestication (Turcotte, Turley, & Johnson, ; Whitehead, Turcotte, & Poveda, ), suggesting that the phenomenon of plants being “disarmed by domestication” may not be as widespread as first thought.…”
Section: Introductionmentioning
confidence: 99%